Low-dose and standard-dose whole-body [18F]FDG-PET/CT imaging: implications for healthy controls and lung cancer patients - Ferrara, Daria; Shiyam Sundar, Lalith Kumar; Chalampalakis, Zacharias; Geist, Barbara Katharina; Gompelmann, Daniela; Gutschmayer, Sebastian; Hacker, Marcus; Kertész, Hunor; Kluge, Kilian; Idzko, Marco; Langsteger, Werner; Yu, Josef; et al. (Frontiers in Physics, 2024)
Aim: High-sensitivity hybrid positron emission tomography (PET) imaging using advanced whole-body (WB) or total-body PET/computed tomography (CT) systems permits reducing injected tracer activity while preserving diagnostic quality. Such approaches are promising for healthy control studies or exploring inter-organ communication in systemic diseases. This study assessed test/retest variations in the fluoro-2-deoxy-D-glucose (FDG) uptake in key organs from low-dose (LD) and standard-dose (STD) [18F]FDG-PET/CT imaging protocols in healthy controls and lung cancer patients. Methods: A total of 19 healthy controls (19–62 years, 46–104 kg, 10 M/9 F) and 7 lung cancer patients (47–77 years, 50–88 kg, 4 M/3 F) underwent [18F]FDG-PET/CT imaging. All subjects were first injected (“test,” LD) with 28 ± 2 MBq FDG and underwent a dynamic (0–67 min post-injection) WB imaging protocol with LD-CT. Then, 90 min post-LD injection, the subjects were repositioned and injected with 275 ± 16 MBq FDG (“retest,” STD). Second LD-CT and STD-CT scans were acquired for healthy controls and patients, respectively. Static images (55–67 min post-injection) were considered for subsequent analysis. The CT images were used to automatically segment the target volumes of interest. Standardized uptake values normalized to the body weight (SUVBW) were extracted for each volume of interest. The mean SUVBW were compared for both LD/STD conditions with paired t-tests. In patients, FDG-avid lesions were manually delineated on LD and STD static images. Effective dose levels were estimated from both the CT and PET acquisitions. Results: Organ-based mean SUVBW were similar between the LD and STD (mean %difference ≤5%) in both healthy controls and cancer patients, except in the heart. Intra-control test/retest variability was significant in the brain, heart, and skeletal muscle (p < 0.05). While 17 lesions were delineated on the STD images of the patients, only 10/17 lesions were identified on the LD images due to increased image noise. Lesion-based mean SUVBW were similar between LD and STD acquisitions (p = 0.49, %difference = 10%). In patients, the effective doses were (1.9 ± 0.2) mSv (LD-CT), (16.6 ± 5.4) mSv (STD-CT), (0.5 ± 0.1) mSv (LD-PET), and (4.6 ± 0.3) mSv (STD-PET). Conclusion: LD and STD [18F]FDG injections in healthy controls and lung cancer patients yielded comparable mean SUVBW, except in the heart. Dose levels may be reduced for [18F]FDG-PET imaging without a loss in mean SUVBW accuracy, promoting LD-PET/CT protocols for studying multi-organ metabolic patterns. In oncology patients, this approach may be hindered by a lower diagnostic quality in the presence of significant noise.